Effects of Resveratrol on Fatty Acid Levels in Serum and Erythrocytes of Rats Administered Potassium Bromate - Keser, Serhat; Yilmaz, Okkes; Tuzcu, Mehmet (Asian Journal of Chemistry, 2010)
Resveratrol is a phytoalexin, highly abundant in skins of red grapes, peanuts and blue berries. The aim of this study is to examine effects of antioxidant resveratrol and carcinogen potassium bromate on the level of fatty acids in serum and erythrocytes of old female Wistar albino rats. In this study, Wistar rats were randomly divided into three groups: (1) control; (2)KBrO3 (80 mg/kg, i.p. single dose) (3) resveratrol + KBrO3 (80 mg/kg KBrO3 i.p. single dose, 33 mg/kg resveratrol, every other day, for 35 days). In serum and erythrocytes, fatty acid levels were measured by gas chromatography. In respect of present results, while stearic and arachidonic acid levels increased in serum of KBrO3, and resveratrol + KBrO3 groups (p < 0.05), same fatty acids levels decreased in erythrocytes of same groups (p < 0.05) when in comparison to control. While oleic acid, linoleic acid and linolenic acid levels increased in erythrocytes of KBrO3 and resveratrol + KBrO3 groups (p < 0.01, p < 0.05), linoleic acid level decreased in serum of same groups (p < 0.05, p < 0.001) in comparison to control. Present results confirmed that oxidation formation in fatty acids of serum and erythrocytes of old female Wistar rats by induced the KBrO3 and its partially protected by the resveratrol. Resveratrol and KBrO3 applications have influenced the amount of important fatty acids that substrates in fatty acids metabolism on duty enzymes.
Keywords: Resveratrol; Potassium bromate; Serum; Erythrocytes; Linoleic add; Stearic acid; Arachidonic acid